Non-viral Gene Therapy for Osteoarthritis - Uzieliene, Ilona; Kalvaityte, Ursule; Bernotiene, Eiva; Mobasheri, Ali (Frontiers in Bioengineering and Biotechnology, 2021)
Strategies for delivering nucleic acids into damaged and diseased tissues have been divided into two major areas: viral and non-viral gene therapy. In this mini-review article, we discuss the application of gene therapy for the treatment of osteoarthritis (OA), one of the most common forms of arthritis. We focus primarily on non-viral gene therapy and cell therapy. We briefly discuss the advantages and disadvantages of viral and non-viral gene therapy and review the nucleic acid transfer systems that have been used for gene delivery into articular chondrocytes in cartilage from the synovial joint. Although viral gene delivery has been more popular due to its reported efficiency, significant effort has gone into enhancing the transfection efficiency of non-viral delivery, making non-viral approaches promising tools for further application in basic, translational and clinical studies on OA. Non-viral gene delivery technologies have the potential to transform the future development of disease-modifying therapeutics for OA and related osteoarticular disorders.